(Re)directing a university storytelling troupe for at-risk elementary students for course credit: a story of embodied empathy, literacy, and personal transformation. Issue 2 (2nd April 2020) - Scott, Julie-Ann
ABSTRACT: This essay maps a professor/director's experience designing and leading a university storytelling troupe that performs for children in local Title 1 elementary schools for course credit. The director begins by applying performance ethnographic and personal narrative research methodology to redesign the course to meet the needs of at-risk children and then explains the process through which the students in the open-enrollment troupe select and adapt literature that is appropriate and meaningful for their audience. The pedagogical and artistic learning objectives seek to foster human connection, understanding, empathy, and equity through a series of well-crafted solo-shows adapted from children's literature.